In situ high-resolution ultrasonic visualization of damage evolution in the volume of quasi-isotropic CFRP laminates under tension. (December 2022) - Morokov, Egor; Titov, Sergey; Levin, Vadim
Abstract: The work is devoted to novel experimental equipment for in situ visualization of damage development in the volume of CFRP under tensile. The acoustic microscope with long-focus probe beam of high-frequency ultrasound (50–100 MHz) was combined with mechanical testing machine. The experimental equipment provides visualization in dynamics of the processes of appearance, growth and transformation of microstructural damages in the volume of the specimen under mechanical loading. The method was validated by 4- and 7-ply quasi-isotropic CFRP laminates with symmetrical round notches. We explore the possibilities of ultrasound imaging for detection of matrix crack opening, and the mechanism of delamination formation with various combination of fiber orientation. According to the ultrasound imaging of the volumetric microstructure, we depicted several mechanisms of damage appearance and evolution under tension. For calculating the level of local deformation in the region with round notches, we applied the digital image correlation (DIC) of ultrasonic scans obtained during the experiment. The DIC data provides more correct values of deformations occurring in the specimen zone with round notches. It was shown that the values in the central area differ significantly from the deformation calculation along the whole length of the specimen, especially under loads close to the critical ones. Graphical abstract: Image 1